The Global Debt Crisis and Its Socioeconomic Implications Creating Conditions for a Sustainable, Peaceful, and Just World - Rabie, Mohamed (Springer International Publishing, 2018)
This fascinating and ambitious book proposes a new strategy ("the Ramo Plan") to tackle the current global socioeconomic crisis. Issuing a direct challenge to the status quo, the author lays out a bold set of policies to overcome the West-East divide and lead us to a more successful and secure future. Alongside the presentation of a new economic approach, this book provides a thorough survey of the major forces behind the decline in economic growth rates. It examines the state of the major world economies, explores the impact of the global debt crisis, identifies the income and wealth gaps in the United States and other countries, and explains the relationship between these issues and the spread of alienation, radicalism and terrorism. Imaginative and refreshing, this is valuable and original reading for students and academics interested in international political economy, economic development, sustainable development, and social economics, as well as global policy, area studies, globalization studies, and international relations.